Tradisi Distribusi Zakat Fitrah kepada Kyai: Kajian Sosial dan Keagamaan Masyarakat Madura - Laila, Zahrotul; Firmansyah, Hendri; Hamim Sultoni, Mohammad (Kartika: Jurnal Studi Keislaman, 2025)
The people of Taddan Village, located in Camplong District, Sampang Regency, recognize zakat fitrah as a religious obligation for Muslims, as it constitutes the third pillar of Islam. However, their comprehensive understanding of zakat fitrah remains limited. The tradition of distributing zakat fitrah to Kyai represents a form of implementation that has been passed down through generations and continues to be preserved in Taddan Village. This study aims to examine the underlying factors behind this tradition, to describe the distribution process, and to assess its role in shaping the community’s social, cultural, and religious life. This research employs a qualitative approach with a descriptive design, focusing on social facts, cultural practices, events, and lived experiences. The findings reveal that the tradition originated from the habit of the Taddan Village community, who gave zakat fitrah to the Islamic boarding schools where their children studied, as an expression of gratitude and respect. Over time, this practice became deeply rooted and evolved into a hereditary tradition. However, when the distribution of zakat fitrah becomes overly centered on Kyai, there is a risk that the poor, who are more in need—receive less benefit. This indicates that the community tends to prioritize fulfilling religious obligations as a form of obedience, without adequately considering the social dimensions, particularly the fairness of distribution and the productive use of zakat fitrah.